Kapit Pisi as mga Kababayang Aeta Pisi Poso ay Ihahandog na Tulong Para Iwas Soil Transmitted Helminth Infection" - Acma, Kathleen Ann; Adolfo, Estee Joy G.; Bautista, Ezekiel Therese S.; Calimot, Andro Dominic A.; Dinopol, Christine Alexis; Legaspi, Marianne C.; Linas, Pearl Joy C.; Lunar, Lanilyn Marie F.; Moises, Rochelle Anne Q.
Soil Transmitted Helminth Infection is one of the most common parasitic infections in the world, and it is considered as a neglected tropical disease which affects poverty-stricken, indigent and marginalized sectors of the community (World Health Organization, 2012). STH is transmitted through the fecal-oral route transmitted by the three most common species of helminths: Ascaris lumbricoides, Trichuris trichiura, and hookworm. In a study conducted in Davao del Norte, Philippines, the cumulative prevalence in indigenous people (IP) school children was significantly higher than in non-IP children with rates at 39.0% and 29.9%, respectively. The Kapit Pisi project aims to decrease the prevalence of soil transmitted helminth (STH) infections among children ages 0-12 years old of Sitio Igtuba, an Aeta community in Brgy. Camangahan, Guimbal, Iloilo. A qualitative stool examination was conducted before project implementation and results show that 56% of the children were positive fo A. Lumbricoides infection, 72% were positive for T. Trichura infection, and 40% are positive for hookworm infection. Fifteen out of the twenty five (60%) children had mixed infection. They were further quantified as light, moderate, and heavy infection. In order to address the problem, the Kapit Pisi project organized a reliable, independent core group for the implementation and monitoring of the project well represented by the members of the community. A series of health education were conducted to increase the knowledge, attitude, and practices among the children through different triggering tools adapted from the Philippine Approach to Total Sanitation. This includes lectures on environmental sanitation, importance of hand washing, and disease transmission. Hygiene kits and slippers were also distributed to the children. Pre and posttest were conducted and results show that the KAP increased by 35% and 36% for children and parents, respectively. A deep well was constructed to provide safe water supply through bayanihan system. The well is already being used for their daily needs except for drinking and food preparation. The pisi poso was not feasible as of the moment because of inadequate water level due to the summer season. Two toilets were installed and ten are currently constructed which was spearheaded by Guimbal through the participation of different sectors of the community.